Assistance In The Utilization Of Affiliate Marketing E-Commerce Shopee And Tiktokshop - Mukhlas, Abdulloh Arif; Prastono, Yahya Sindy; Solihah, Maratus; Agustin, Ellyza Tania; Manisa, Siti; Fitrianingtyas, Pramudita Putri (LPPM, STAI Al-Azhar Menganti, 2023)
E-commerce, or electronic commerce, is the process by which sellers and buyers interact to conduct transactions over the internet. Using e-commerce platforms such as Shopee and TikTokShop provides many benefits for businesses, such as easing the marketing process with lower costs, reaching consumers without geographical restrictions, and opening up potential for future business growth. However, for some housewives and teenagers today, marketing is still done through traditional methods such as word of mouth and is only limited to the surrounding environment, so they have not utilized digital or online marketing. Therefore, this Community Service Program (PKM) is designed to provide knowledge and training to the community, especially mothers (PKK) and teenagers in Tulung Kedamean, Gresik Regency, on how to become Shopee and TikTokShop affiliates. Through this program, they can promote certain products through social media and earn a commission from every sale that occurs through their affiliate link. The method used in this mentoring program is Asset Based Communities Development, which is a theory that prioritizes the utilization of existing assets and potential around by utilizing e-commerce affiliate marketing in this digital era. The results of this mentoring activity are expected to provide information and insights to the government and related parties in designing programs that support the economic empowerment of mothers and youth in the village through the use of e-commerce platforms.